The Deficiency of CH3NH3PbI3 Solar Cells Performance Under High Relative Humidity - Nurul Ain , Manshor; Zinab, H. Bakr; Rajan, Jose (Universiti Malaysia Pahang, 2016)
With the consideration of humidity effect, the deficiency of CH3NH3PbI3 solar cells performance under high relative humidity is predicted. The efficiency limitation was studied in order to enhance the perovskite solar cell (CH3NH3PbI3) performance. To understand this convincing prediction, perovskite solar cells were synthesis, fabricated and characterized in high humidity condition. The role of humidity in degradation and then decline the perovskite solar cell performance are also clarified due to the humidity sensitive nature of these perovskite, their thin films are often prepared in-situ which may hinder their mass production.